Precision in Setting Cancer Prevention Priorities: Synthesis of Data, Literature, and Expert Opinion - Girschik, Jennifer; Miller, Laura Jean; Addiscott, Tony; Daube, Mike; Katris, Paul; Ransom, David; Slevin, Terry; Threlfall, Tim; Weeramanthri, Tarun Stephen (Frontiers in Public Health, 2017)
Cancer will continue to be a leading cause of ill-health and death unless we can capitalize on the potential for 30-40% of these cancers to be prevented. In this light, cancer prevention represents an enormous opportunity for public health, potentially saving much of the pain, anguish and cost associated with treating cancer. However, there is a challenge for governments, and the wider community, in prioritizing cancer prevention activities, especially given increasing financial constraints. This paper describes a method for identifying cancer prevention priorities. This method synthesizes detailed cancer statistics, expert opinion and the published literature for the priority setting process. The process contains four steps: assessing the impact of cancer types; identifying cancers with the greatest impact; considering opportunities for prevention; and combining information on impact and preventability. The strength of our approach is that it is straightforward, transparent and reproducible for other settings. Applying this method in Western Australia produced a priority list of seven adult cancers which were identified as having not only the biggest impact on the community but also the best opportunities for prevention. Work conducted in an additional project phase went on to present data on these priority cancers to a public consultation and develop an agenda for action in cancer prevention.